2020
DOI: 10.2174/1568026619666191127144336
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antibacterial Activity of Sulfonamides Derived from Carvacrol: A Structure-Activity Relationship Study

Abstract: Background: Bacterial resistance to antibiotics is a growing problem in all countries and has been discussed worldwide. In this sense, the development of new drugs with antibiotic properties is highly desirable in the context of medicinal chemistry. Methodology: In this paper we investigate the antioxidant and antibacterial potential of sulfonamides derived from carvacrol, a small molecule with drug-like properties. Most sulfonamides had antioxidant and antibacterial potential, especially compound S-6, deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Even though many molecules in heterocyclic compounds have antioxidant and antidiabetic activity, benzoxazole is one of the most potent moieties for biological evaluation, including both antioxidant [2] and anti-diabetic [3] assay. Literature survey also revealed that the substitution like sulfonamide group shows a variety of biological activities like anti-microbial, anti-inflammatory [4], antioxidant [5], antidiabetic [6], and anticancer [7] activities. The substitutions like chloro [2], nitro [2] also have good biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Even though many molecules in heterocyclic compounds have antioxidant and antidiabetic activity, benzoxazole is one of the most potent moieties for biological evaluation, including both antioxidant [2] and anti-diabetic [3] assay. Literature survey also revealed that the substitution like sulfonamide group shows a variety of biological activities like anti-microbial, anti-inflammatory [4], antioxidant [5], antidiabetic [6], and anticancer [7] activities. The substitutions like chloro [2], nitro [2] also have good biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonamides derived from carvacrol have been investigated recently, for which antibacterial properties ( Oliveira et al, 2020 ) and potential candidates for the development of drugs for the treatment of Alzheimer's disease have been reported ( De Souza et al, 2020 ). As mentioned above and due to the analgesic and anti-inflammatory potential of carvacrol, in this research, the antinociceptive potential of these sulfonamides was investigated.…”
Section: Introductionmentioning
confidence: 99%